2012
DOI: 10.1167/iovs.12-9837
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vein Pulsation Is in Phase with Intracranial Pressure and Not Intraocular Pressure

Abstract: During pulsation, central retinal vein collapse occurs in time with IOP and ICP diastole. Venous collapse is not induced by intraocular systole. These results suggest that ICP pulse pressure dominates the timing of venous pulsation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 30 publications
2
70
0
2
Order By: Relevance
“…The remaining 12 studies enrolling 546 participants identified in our literature search were included in our meta-analysis (Table 1). 2,4,5,11,15,16,19,24,25,31,32,35,36 Although all of these 12 studies contributed to the calculation of a pooled estimated correlation coefficient, only 4 presented outcomes required for the calculation of summary diagnostic accuracy estimates (Table 2). 16,19,25,36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 12 studies enrolling 546 participants identified in our literature search were included in our meta-analysis (Table 1). 2,4,5,11,15,16,19,24,25,31,32,35,36 Although all of these 12 studies contributed to the calculation of a pooled estimated correlation coefficient, only 4 presented outcomes required for the calculation of summary diagnostic accuracy estimates (Table 2). 16,19,25,36 …”
Section: Resultsmentioning
confidence: 99%
“…36 In half of the included studies, invasive ICP measurement was obtained through lumbar puncture (LP) 11,15,19,25,31,32 while the remainder measured ICP through intracranial monitors. 2,4,5,16,24,35,36 The interval between IOP and ICP measurement ranged from simultaneous measurements 4,5,16,24,35,36 to up to 5 hours. 11 Among studies reporting diagnostic accuracy estimates, the thresholds for assigning elevated IOP and intracranial hypertension were defined as a measurement greater than 20 cm H 2 0.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a posture-dependent change in TLCPD. However, simultaneous assessment of the IOP and ICP is sparse [17][18][19][20] . Changes in TLCPD as a function of posture has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Morgan and colleagues demonstrated in a previous study a difference in the phasing of the IOP curve and the phasing of the CSFP curve with respect to the cardiac cycle, with the ICP curve reaching its height earlier than the CSFP curve (Morgan et al 2012). It was then wondered whether these physiological short-term changes in the TLCPD, potentially even resulting in short-term reversals of the TLCPD and thus in a swinging TLCPD, may physiologically be needed to allow the retrograde axoplasmic flow entering the eye (Jonas et al 2012).…”
Section: Referencesmentioning
confidence: 96%